The contribution of budgetary and accounting reform to the Implementation of International Public Sector Accounting Standards (IPSAS) in Algeria - Chougui, Tarek; Redjem, Khaled (The International tax journal, 2025)
The study aims to highlight the legislative reforms undertaken by Algeria through Organic Law 15-18 related to finance laws and Law 07-23 concerning public accounting, and to assess their contribution to adopting or implementing International Public Sector Accounting Standards (IPSAS). The study reached significant findings, indicating that the legislative reforms initiated by Algeria represent an important step toward applying IPSAS in the public sector. However, these reforms must be accompanied by other structural, administrative, and economic reforms, among others. This entails addressing a range of challenges and difficulties that the relevant authorities must confront and overcome to effectively implement IPSAS in Algeria’s public sector.